Impact of Mg2+ and Al3+ Substitutions on the Structural and Electrochemical Properties of NASICON‐NaxVMn0.75M0.25(PO4)3 (M = Mg and Al) Cathodes for Sodium‐Ion Batteries. Issue 45 (20th October 2020) - Ghosh, Subham; Barman, Nabadyuti; Senguttuvan, Premkumar
Abstract: Sodium superionic conductor (NASICON)‐Na4 VMn(PO4 )3 (NVMP) cathode is attractive for sodium‐ion battery application due to its reduced cost and toxicity, and high energy density (≈425 Wh kg −1 ). However, it exhibits significant polarization, limited rate and cycling performances due to its lower electronic conductivity and formation of Jahn–Teller active Mn 3+ during cycling. In this report, a chemical approach is presented to partially replace Mn 2+ of the NVMP framework by Mg 2+ and Al 3+ substitutions. The Mg‐ and Al‐substituted NVMP cathodes present smoother voltage profiles, facile sodium (de)intercalation, enhanced rate performances (80 mA h g −1 at 5C rate) and capacity retention (≈96% after 100 cycles) in comparison with the unsubstituted sample. Their enhanced performances are attributed to suppressed Jahn–Teller effect, increased covalent character and sodium ion vacancies of the NASICON framework. These results highlight the significance of fine tuning the chemical compositions to attain high performance NASICON cathodes. Abstract : The influence of Mg 2+ and Al 3+ chemical substitutions on the structural and electrochemical properties of sodium superionic conductor (NASICON)‐Na4 VMn(PO4 )3 is studied. The Mg‐ and Al‐substituted cathodes provide enhanced rate performances (80 mA h g −1 at 5C rate) and capacity retention (≈96% after 100 cycles), which is due to suppressed Jahn–Teller effect, increased covalent character, and sodium ion vacancies of the NASICON framework.